Pengaruh Keadilan Organisasional Terhadap Kinerja Karyawan Dimediasi LMX (Leader-Member Exchange) Dilihat dari Aspek Gender - Widya, Alifah; Tjahjono, Heru Kurnianto; Mustafa, Zainal; Prajogo, Wisnu (JURNAL BISNIS STRATEGI, 2021)
The purpose of this article is to examine the mediating role of leader-member exchange in the relationship between organizational justice and employee performance in terms of gender. This article focuses on ATLM (Medical Laboratory Technologist) regarding organizational justice practices and the Leader-Member Exchange relationship and how these perceptions predict employee performance and how it affects employee gender. The sample used was 191 ATLM in type C hospitals in the D.I. Yogyakarta and Central Java. The results of this study will help ATLM to foster greater employee value and teamwork among employees by implementing organizational justice practices.